EROSIONAL WEAR OF THE LOAD CARRYING CANVAS OF BURNING MACHINES UNDER THE INFLUENCE IRON ORE PELLETS - Malinovskyi, Yurii; Uchytel, Oleksandr; Panchenko, Hanna; Vlasenkov, Dmyro; Oliinyk Svitlanа (Problems of Friction and Wear, 2023)
The load-carrying belt of conveyor machines for clods of iron ore concentrate operates in a complex, aggressive dust and gas environment and cyclic "heating-cooling" modes. At the same time, the constituent elements of the load-bearing fabric - gratings also work under the influence of shock and abrasive loads, which leads to their intensive wear, as well as an increase in the regulated working gaps between adjacent gratings, and, therefore, to their premature replacement. In order to predict the degree of wear of the working surfaces of parts (grills), numerical models have been developed at the micro, macro, and meso levels. These models work in various combinations, but in the given conditions of operation of burning machines, due to the specifics of their work, meso- and micro-models rarely appear. The results of the analysis of the defects of the grates, which have failed, indicate the manifestation of macro-models, the schematization of which takes place mainly in the form of an erosive wear model. On the basis of macro models, Bitter’s dependences were modified to calculate the degree of erosive wear of grates, and it was also established that to significantly reduce the degree of wear of pallets, it is recommended to use drum-type loading devices that ensure unloading of material with an angle of attack α=35÷45°. At the same time, the best recommended material for grates is steel 30Х14Г8Ю2Л.